International bibliography on coastal geomorphology (1983-1986) - International Geographical Union, Commission on the Coastal Environmen (Investigaciones Geográficas: Una mirada desde el sur, 1986)
The Commission on the Coastal Environment, one of the oldest commissions of the lnternational Geographical Union, is issuing a new volume of its quadrennial International Bibliography on Coastal Geomorphology, whose editor is Professor J.F. Araya-Vergara from the University of Chile. This publication represents only one of the many activities of the Commission on the Coastal Environment. For the 1986-1988 period, several research projects have been carried out about the following topics: beach-dune system interactions, shore response to sea level rise, dynamics of coarse clastic beaches, cheniers, human impact on coastal lagoons and coral reefs, recreation uses in coastal areas, coastal hazards, nature of national policies for coastal open space. Publications of the main results of those projects will proceed as soon as enabling funds have been identified. Several meetings have been organized by the Commission during the last few years: Rocheford (France), 1984; Aix - en - Provence (France), 1985; Tallinn (USSR), 1986; Barcelona (Spain), 1986; Portland (USA), 1987 ; London (England), 1987. Guide-books and proceedings are available for most of those symposia. Six issues of the Newsletter edited by Professor Norbert P. Psuty from Rutgers - The State University of New Jersey (USA) have been issued since 1984. More than 450 corresponding members around the world are receiving the liaison bulletin aimed to facilitate exchange of information. I would like to express my sincere thanks to Professor J.F. Araya-Vergara for having accepted to edit this new volume of the lnternational Bibliography and the Faculty of Architecture and Urbanism (Departament of Geography) of the University of Chile for having funded its publication.